Comparison of Tendon Development Versus Tendon Healing and Regeneration - He, Peiwen; Ruan, Dengfeng; Huang, Zizhan; Wang, Canlong; Xu, Yiwen; Cai, Honglu; Liu, Hengzhi; Fei, Yang; Heng, Boon Chin; Chen, Weishan; Shen, Weiliang (Frontiers in Cell and Developmental Biology, 2022)
Tendons connect muscles to bone and transmit the force generated during muscle contraction to the skeleton; this process is crucial for the architecture, functionality and biomechanics of the musculoskeletal system. Tendon development is completed within the embryonic stage, and tendons at different locations within the body have different embryonic origins. The tendons in the cranium, limbs and trunk are derived from neural crest cells of the ectoderm, the paraxial mesoderm, and the lateral plate mesoderm respectively. The development of tendons is regulated by various transcription factors and signaling pathways, as well as mechanical stimulation, which takes effect at specific stages during tendon development. Scx (scleraxis) plays a key role in this process, while the TGFβ and FGF signaling pathways are indispensable as well. These synergistically form a signaling network that regulates tendon development. The process of tendon repair is different in adults and embryos. When a tendon is damaged at the embryonic stage, it can regenerate in the same way that tendons develop. However, scar-associated healing occurs in adults. Ideally, the regenerative process of tendon injury repair should be a recapitulation of development at the embryonic stage. However, although the process of adult tendon repair and regeneration share some similarities with development, there are also many differences. These often result in poor repair results. At present, several approaches are being investigated to improve tendon healing, notably stem cell-based therapy. The study and comparison of tendon development and repair process can thus provide references and guidelines for treatment of tendon injuries.